Genetic diversity of dengue virus serotypes 1 and 2 in the State of Paraná, Brazil, based on a fragment of the capsid/premembrane junction region - Ana Caroline Dalla Bona; Adriana Lacerda Twerdochlib; Mário Antônio Navarro-Silva (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: The precise identification of the genetic variants of the dengue virus is important to understand its dispersion and virulence patterns and to identify the strains responsible for epidemic outbreaks. This study investigated the genetic variants of the capsid-premembrane junction region fragment in the dengue virus serotypes 1 and 2 (DENV1-2). METHODS: Samples from 11 municipalities in the State of Paraná, Brazil, were provided by the Central Laboratory of Paraná. They were isolated from the cell culture line C6/36 (Aedes albopictus) and were positive for indirect immunofluorescence. Ribonucleic acid (RNA) extracted from these samples was submitted to the reverse transcription polymerase chain reaction (RT-PCR) and nested PCR. RESULTS: RT-PCR revealed that 4 of the samples were co-infected with both serotypes. The isolated DENV-1 sequences were 95-100% similar to the sequences of other serotype 1 strains deposited in GenBank. Similarly, the isolated DENV-2 sequences were 98-100% similar to other serotype 2 sequences in GenBank. According to our neighbor-joining tree, all strains obtained in this study belonged to genotype V of DENV-1. The DENV-2 strains, by contrast, belonged to the American/Asian genotypes. CONCLUSIONS: The monitoring of circulating strains is an important tool to detect the migration of virus subtypes involved in dengue epidemics.